Environmental management accounting : information support of company management - Hyršlová, Jaroslava; Špaček, Ladislav; Hájek, Miroslav (Univerzita Pardubice, 2006)
The decision-making tasks in a company require high quality information support. Under the conversion to the sustainable development scheme where the behavioural patterns of producers as well as consumers change, and where the approach of companies towards environment has a direct influence on the company's prosperity, environmental management accounting becomes a substantial tool for the support of decision-making processes - namely that component of the environmental accounting system which is primarily focused on meeting the information demands of the management. This paper focuses on the information demands of the management in the field of environmental performance and its influence on the company's economic performance.
Keywords: environmentální management; environmentální účetnictví; informační potřeby; rozhodovací procesy